Evaluasi Transportasi Angkutan Umum Dan Keselamatan Akibat Adanya Transportasi Online di Kota Makassar - Ni'am, Haerun; Nurdin, Abd. Rahim; Yunianti, Nur Hadijah (Program Studi Teknik Sipil Universitas Bosowa, 2024)
The aim of the research is to determine the comparison of costs, time and safety between public transportation and online transportation. Transportation or transportation is a means of moving goods or people from one place to another as desired. In general, people now know 2 types of transportation, namely online transportation and conventional transportation. Where application-based online transportation is the transfer of goods and people from the place of origin to the destination. It should be understood together that the flow of technological progress is a necessity that we inevitably have to follow. So that application-based online transportation is a transportation service that utilizes technological advances. Technology was created with the aim of facilitating all human activities that are carried out daily, not so long ago, so many demonstrations began to appear in various areas in Makassar carried out by the conventional public transport drivers to oppose the operation of the online transportation business in Indonesia, especially the city of Makassar.